Temporal variation of the sea urchin Diadema mexicanum population density at Bahias de Huatulco, Western Mexico - Benítez-Villalobos, F.; Domínguez y Gómez, M. T.; López Pérez, R. A. (Revista de Biología Tropical, 2008)
Sea urchins of the genus Diadema play an important role as controlers of algal growth in coral reef and rocky reef communities, but high densities cause bioerosion of the reef framework. Between January 2006 and February 2007 (except April, July and August), population densities and mean test diameter of Diadema mexicanum were determined at Isla Montosa, La Entrega, Isla Cacaluta and San Agustín, Bahías de Huatulco, Mexico. Mean density of the sea urchins was relatively constant through time at all localities: lowest at San Agustín (0.26±0.13 ind.m-2) and highest at La Entrega (4.17±1.4 ind.m-2). There were significant differences between La Entrega and other localities. Mean test diameter ranged between 4.41±0.88 cm (Isla Cacaluta) and 4.72±0.27 (San Agustin), and did no vary significantly between localities, but there were monthly variations. Test diameter agrees with other studies. The calculated amount of CaCO3 removed by D. mexicanum showed variations between localities. The lowest rate of bioerosion occurred at San Agustín (0. 25 kg.m-2.yr-1 ), and the highest at La Entrega (4 kg.m-2.yr-1). The recent urchin population decrease means a reduction in their removal of coral CaCO3: 5.55% to 2.36% at Isla Cacaluta, 5.08% to 1.40% at San Agustin and 16.59% to 3.08% at Isla Montosa. The only locality where bioerosion increased was La Entrega, from 27.04 % to 33.05 %. This reduction of urchin activities could be beneficial for coral reef growing and recovery from stress, nevertheless it could also signify an increase in algal biomass and competition with corals for light and space. We recommend a permanent monitoring and evaluation of population densities of D. mexicanum and fishes, as well as coral and algal cover at the area, to discern if changes in sea urchin densities in Bahias de Huatulco are a continuous phenomenon, or part of a natural cycle of increments and reductions. Rev. Biol. Trop. 56 (Suppl. 3): 255-263. Epub 2009 January 05.